Equilibrium Studies on Binary Chelate Formation ofVitamin-U with Some Alkaline Earth Metal Ions - Joshi, J.D.; Vora, J.J.; Sharma, Sangita; Chaudhary, R.H.; Patel, R.A.; Gurjar, J.G.; Patel, D.R. (Asian Journal of Chemistry, 2010)
The present paper describes pH-metric study on formation constant of binary complexes of alkaline earth metal ions (Mg2+, Ca2+, Sr2+ and Ba2+), with vitamin-U carried out at constant temperature 25 ± 0.1ºC and ionic strength μ = 0.2 M dm–3 (NaClO4). Various factors influencing the formation and stabilities of binary complexes have been discussed.